2008
DOI: 10.1016/s1875-2136(08)70251-1
|View full text |Cite
|
Sign up to set email alerts
|

Particularities of peripheral arterial disease managed in vascular surgery in the French West Indies

Abstract: This study highlights clear differences regarding the presentation, localization and associations of PAD in the West Indies subjects managed in vascular surgery, especially with a severe infragenicular disease, even in claudicants. This study suggests the effect of a different distribution of risk factors as well as other ethnic and socio-economic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…However, some reports show a lower prevalence of tobacco use among women with PAD than among men. [28][29][30] There is a connection between the development of PAD and C-reactive protein (CRP) levels. 31 Elevated levels of CRP may be a marker for PAD severity.…”
Section: Risk Factors For Pad Among Womenmentioning
confidence: 99%
“…However, some reports show a lower prevalence of tobacco use among women with PAD than among men. [28][29][30] There is a connection between the development of PAD and C-reactive protein (CRP) levels. 31 Elevated levels of CRP may be a marker for PAD severity.…”
Section: Risk Factors For Pad Among Womenmentioning
confidence: 99%
“…45 Previous studies have indicated that African Caribbeans and South Asians seemed to report more distal PAD than the general population. 18,85,159,160,163 In Indians, thromboangiitis obliterans appears to contribute to this increase. 164 In a previous hospital-based study in India, this disease reflects the younger age of presentation of patients with distal PAD.…”
Section: Pad Distribution In Ethnic Groupsmentioning
confidence: 99%
“…We find that there is a distal damage more frequent than proximal. This has been demonstrated in other recent studies such as the study of De Neuville in 2008, including 754 patients, focused on the PAD description of the West Indian subject (France) by analysis of a surgical employment of database, which showed that hemodynamic damages affected the infrapopliteal level in 86% of cases, the femoro-popliteal axis in 51%, but in only 7% of cases the aortoiliac level; the Copart register in 2013, 60.2% of patients at Toulouse University Hospital and 73.5% patients of Bordeaux and Limoges University Hospital Centers have infra-popliteal lesion and in 2014, Lavinia Belaye, in a work aimed at identifying the predominant localization of PAD, and the CVRFs influencing its topography, found the predominance of distal PAD in the 268 patients included in the study, 84.70% patients had an infra-popliteal implication, and respectively a popliteal implication 55.22%, femoral 69.02% and aortoiliac 42.91% [7][8][9].…”
Section: Infra Popliteal Axis Lesionmentioning
confidence: 95%